Clinical and functional outcomes of extracorporeal shock wave therapy in isolated medial epicondylitis - Turhan, Yalçın; Arıcan, Mehmet; Karaduman, Zekeriya Okan (The European Research Journal, 2019)
Objective: To evaluate the effectiveness of extracorporeal shock wave therapy (ESWT) for the patients with isolated medial epicondylitis refractory to other conservative methods. Methods: A retrospective analysis of 57 patients with the diagnosis of isolated medial epicondylitis refractory to conservative measures was done. 36 of them who met our eligibility criteria were included. Patients were subjected to three sessions of extracorporeal shock wave therapy with 2000 pulses per a session in a dose of 0.06-0.12 mJ/mm2. Pain and clinical/functional scores were measured by visual analogue scale (VAS) and Quick-Disabilities of the Arm, Shoulder and Hand (Q-DASH) respectively before the treatment and at 1st week and 12th week of the last session. Results: Mean age of the patients was 47.3 (25-67) years and there was a higher female presentation (24 female and 12 male patients). The VAS scores were improved from a mean of 7.8 before the treatment to 5.3 at 1st week (p < 0.001) and to 2.9 at 12th week (p < 0.001). Also the results of the Q-DASH showed a mean improvement from 50.4 before the treatment to 27.1 at 1st week (p < 0.001) and 9.6 at 12th week (p < 0.001). There were no significant differences in the improvements of VAS and Q-DASH scores by the time between the male and female patients. Conclusion: According to the results of this study which will be one of the limited studies about isolated medial epicondylitis; ESWT is a good conservative treatment option for medial epicondylitis in refractory cases like in lateral epicondylitis.